A corpus-based approach to the translation of conceptual metaphors in legal language: Chinese Yuān (冤) and English 'Injustice', 'Wrong' and 'Tort'. (4th March 2021) - Mannoni, Michele
ABSTRACT: Yuān (冤) is a Chinese word literally meaning 'bent' which translates into English as 'injustice', 'wrong' and 'tort'. It realises various conceptual metaphors in Chinese, such as yuan is bent, yuan is dirty, and yuan is dark. How does the English translation change these conceptual metaphors and their reception by target text readers? This study takes a Descriptive Translation Studies approach to answer this question. First, it introduces the methods of retrieving and analysing linguistic data, such as corpus search, and the principle of Cognitive Equivalence. Second, it shows the metaphors that yuān realises in Chinese and those realised by its translations in English, and compares their legal meanings. This study has found that 'injustice', 'wrong' and 'tort' are bent, as yuān is, although 'tort' is fully lexicalised and does not activate this mapping in contemporary English. None of the translations for yuān maps dirtiness and darkness onto the corresponding abstract notions. The legal meanings of these words in the two languages are also significantly different.